The significance of glycolysis in tumor progression and its relationship with the tumor microenvironment - Zhou, Daoying; Duan, Zhen; Li, Zhenyu; Ge, Fangfang; Wei, Ran; Kong, Lingsuo (Frontiers in Pharmacology, 2022)
Glycolysis is a known modulator of tumorigenesis and tumor development. The tumor microenvironment (TME) is a complex niche whereby tumor cells survive and develop, and it constantly interacts and co-evolves with other tumor cells. In recent years, there is a renewed interest in glycolysis and TME. This review discussed the significance of glycolysis in tumor development, its association with the TME, and potential glycolysis-targeted therapies, in order to provide new ideas for clinical tumor treatments.